Optimalisasi Pengelolaan Barang Milik Negara Untuk Pendanaan Ibu Kota Negara Baru - Sugiarto, Laga; Hidayat, Arif; Aqila, Firstia Qhaska; Hakim, Putri Balqis Nuril (Peneliti.net, 2025)
The relocation of the capital city from it’s current location to a newly designated site necessitates comprehensive financing strategies. Understanding non-state budget (non-APBN) financing methods for the new capital helps deepen the understanding of the relocation financing process. However, research on financing the new capital city, especially through non-APBN schemes involving the management of state-owned assets, is still limited. This study aims to explore how the relocation of the new capital is financed through non-APBN methods, particularly through the management of state-owned assets. The research employs a library study approach, gathering information from diverse sources such as scientific articles and reports from relevant institutions, and utilizes a qualitative descriptive method. It will examine various non-APBN financing mechanisms for the new capital, with a specific focus on state-owned asset management. The study concludes that optimizing the management of state-owned assets, alongside providing fiscal facilities, must comply with legal regulations to be effective.